Stability in Aqueous Solution of a New Spray-Dried Hydrocolloid of High Andean Algae Nostoc sphaericum - Choque-Quispe, David; Ligarda-Samanez, Carlos A.; Choque-Quispe, Yudith; Froehner, Sandro; Solano-Reynoso, Aydeé M.; Moscoso-Moscoso, Elibet; Carhuarupay-Molleda, Yakov Felipe; Peréz-Salcedo, Ronald (Polymers, 2024)
There is a growing emphasis on seeking stabilizing agents with minimal transformation, prioritizing environmentally friendly alternatives, and actively contributing to the principles of the circular economy. This research aimed to assess the stability of a novel spray-dried hydrocolloid from high Andean algae when introduced into an aqueous solution. Nostoc sphaericum freshwater algae were subject to atomization, resulting in the production of spray-dried hydrocolloid (SDH). Subsequently, suspension solutions of SDH were meticulously prepared at varying pH levels and gelling temperatures. These solutions were then stored for 20 days to facilitate a comprehensive evaluation of their stability in suspension. The assessment involved a multifaceted approach, encompassing rheological analysis, scrutiny of turbidity, sedimentation assessment, ζ-potential, and measurement of particle size. The findings from these observations revealed that SDH exhibits a dilatant behavior when in solution, signifying an increase in with higher shear rate. Furthermore, it demonstrates commendable stability when stored under ambient conditions. SDH is emerging as a potential alternative stabilizer for use in aqueous solutions due to its easy extraction and application.